2008
DOI: 10.1260/174795408784089432
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Constraints to Train Decision Making in Rugby Union

Abstract: This paper focuses on the paradoxical relationship between game unpredictability and the certainty of players' actions in team ball sports. Our research on this relationship leads us to suggest a method for training decision making, which we exemplify in the team sport of Rugby Union. The training methodology is based on application of theoretical insights from Ecological Psychology Complex Dynamical Systems and the Constraints-Led Approach. The paper starts with a critical overview of traditional approaches t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
151
0
20

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(172 citation statements)
references
References 12 publications
1
151
0
20
Order By: Relevance
“…The achievement of a more advanced position in the field can be simply understood as successful performance and can be evaluated by the degree of territorial gain by assessing the position reached with the ball and its behaviour over time, i.e., its dynamics. Other studies have also shown that the analysis of the dynamics of a single variable could reflect the global dynamics of an entire neurobiological system (e.g., Vereijken et al, 1997) and of the dyadic interactions between team games players (e.g., Passos et al, 2008). Previous studies on the dynamics of decision making behaviours in sport have been mainly focused on team sports, typically in 1vs1 interactions (e.g., Araújo, Davids, Bennett, Button, & Chapman, 2004;Davids et al, 2006), or in dyadic sports (e.g., squash by McGarry et al, 2002).…”
Section: Collective Behaviour Conveyed By Distance Gained Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The achievement of a more advanced position in the field can be simply understood as successful performance and can be evaluated by the degree of territorial gain by assessing the position reached with the ball and its behaviour over time, i.e., its dynamics. Other studies have also shown that the analysis of the dynamics of a single variable could reflect the global dynamics of an entire neurobiological system (e.g., Vereijken et al, 1997) and of the dyadic interactions between team games players (e.g., Passos et al, 2008). Previous studies on the dynamics of decision making behaviours in sport have been mainly focused on team sports, typically in 1vs1 interactions (e.g., Araújo, Davids, Bennett, Button, & Chapman, 2004;Davids et al, 2006), or in dyadic sports (e.g., squash by McGarry et al, 2002).…”
Section: Collective Behaviour Conveyed By Distance Gained Dynamicsmentioning
confidence: 99%
“…Within these playereenvironment interactions, the balance of contestability and continuity, coordination and competition, coexist in a complementary way and are believed to be depicted in team's displacement trajectory during performance. This perspective brings about the need to describe and explain the pattern forming dynamics of system agents over time (Passos, Araújo, Davids, & Shuttleworth, 2008). In rugby union, a chief task constraint on decision making and actions of players is the backward pass (International Rugby Board, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Such increased attention in the literature regarding the issue of the performer-environment, an issue which had been seldom addressed, has been recognised and focuses on how specific variables change how a system [e.g. learner (s)] ultimately behaves (Magill, 2007).With a key construct of non-linear pedagogy being the grouping of humans as a class of non-linear dynamical systems (Smith & Thelen, 2003;Davids et al, 2008). In a sporting context this describes players as learning through being complex adaptive systems and is underpinned by both the 'constraints led approach ' (Renshaw et al, 2010), and Dynamical Systems Theory (Handford et al, 1997).…”
mentioning
confidence: 99%
“…In a sporting context this describes players as learning through being complex adaptive systems and is underpinned by both the 'constraints led approach ' (Renshaw et al, 2010), and Dynamical Systems Theory (Handford et al, 1997). In advocating nonlinear forms of pedagogy where multiple choices evoke complex patterns of learning, it is accepted that learning is not predictable and therefore cannot be adequately explained through simplified models (Chow et al, 2006;Davids et al, 2008) Responding to fluctuations primes the creativity of players because they have to source solutions leading to "the generation of high-quality, original, and elegant solutions to complex, novel, ill-defined problems" (Mumford et al, 2012, p.30). Therefore in establishing a set of circumstances, a player can systematically learn from his/her environment by "observing its surroundings, reacting to it by probing, and observing the environment and subsequently evaluating the success of its reaction" (Newell, 1986, p.348).…”
mentioning
confidence: 99%
See 1 more Smart Citation